Seepage Behavior of Fractures in Paleogene Sandstone Reservoirs in Nanpu Sag, Bohai Bay Basin, Eastern China - Wang, Zhaosheng; Muhtar, Meiri; Xu, Donghao; Fang, Jinchuan; Li, Jing; Liu, Daojie; Zhang, Zhenguo; Gao, Lianfeng (Frontiers in Earth Science, 2021)
Natural fractures play an important role in seepage system of Paleogene sandstone reservoirs at Nanpu Sag. Characteristics and formation mechanism of natural fractures and stress-sensitivity permeability are comprehensively investigated and their impact on water injection is discussed based on core and log data (FMI and diplog data) as well as stress-sensitivity permeability measurement. Results show that high-angle shear fractures are widely developed in the study area, which were primarily developed in the late Paleogene and late Neogene. They can be divided into two groups, i.e., NE-SW strike one, followed by NW-SE strike one. The present maximum horizontal principal stress is orientated at N60°-80°E, approximately parallel to the NE-SW fractures those contribute greatly to the seepage system at the early development stage of oilfield. Fractures in the study area are characterized by obvious stress-sensitivity permeability, which is closely related to fracture aperture and throat size and can be divided into three phases. It is necessary to regular well pattern based on fracture dynamic parameters at different development stages of fractured reservoir, since the occurrence of fractures enhances the stress sensitivity of permeability.